Pengaruh Pemberian Terapi Latihan Metode Schroth Terhadap Skoliosis Pada Usia 10-12 Tahun Di Sekolah Dasar Negeri 1 Blulukan - Adillani, Muharromah; , Dwi Rosella K, S.St FT., M.Fis; , Dwi Kurniawati, SSt.FT (2015)
Background: Scoliosis is a sideways aberration of spine which is a deformity (deviation) of a disease that can be caused by nonstructural and structural. This scoliosis is usually forming "C" or "S" curve. The pattern codes on scoliosis are: code for 3 and 4 (curve) : 3 for curve that's huge on the thoracic, 4 for curve that's huge on the lumbar, and C and CP : C for curve that's only on spine, CP for curve that's on spine and followed by elevation on the pelvis. Three shapes of structural scoliosis are : idiopathic scoliosis, congenital scoliosis, and neuromuscular scoliosis. Scoliosis can be divided into : mild scoliosis : cobb angle 10-25°, moderate scoliosis : cobb angle 26-40° and severe scoliosis : cobb angle >50°. The symptoms of scoliosis are : the spine curves abnormally on the sideway, shoulder left and right hips are uneven, pelvic left and right hips are uneven, spine pain, tiredness on the spine after sitting or standing for long time. In this research this research is using schroth method therapy training to reduce the level of curvature on vertebrae toward the scoliosis problem. Research Objective : The purpose of this research is to understand the effect of schroth method training therapy toward scoliosis on age of 10-12. Research Method : This research is using pre-experimental method with the quasi experimental and the research design is design pre and post test one group design. The number of the sample is 12 samples and the sampling is using purposive sampling method which means that the sample is taken purposively in accordance to the inclusive and exclusive criteria. Research Result: Data obtained abnormally distributed, the statistical test using wilcoxon test is to understand the effect of pre and post test on the treatment. Test result acquires total score of schroth method training therapy which there is a significant change toward the degradation of scoliosis curve. Conclusion: With the results above it can be concluded that there is a positive effect on scoliosis. The change in the degree of scoliosis curve on age of 10-12 in Blulukan 1 Public Elementary School. This research is expected to be continued and useful for researcher, medical personnel, or society in general. Keywords: Scoliosis, Schroth Method Training Therapy